Design and Analysis of the First BOWS Contest. (17th October 2007) - Piva, A.; Barni, M.
Abstract : The break our watermarking system (BOWS) contest was launched in the framework of the activities carried out by the European Network of Excellence for Cryptology ECRYPT. The aim of the contest was to investigate how and when an image watermarking system can be broken while preserving the highest possible quality of the content, in the case the watermarking system is subject to a massive worldwide attack. The great number of participants and the echo that the contest has had in the watermarking community contributed to make BOWS a great success. From a scientific point of view, many insights into the problems attackers have to face with when operating in a practical scenario have been obtained, confirming the threat posed by the sensitivity attack, which turned out to be the most successful attack. At the same time, several interesting modifications of such an attack have been proposed to make it work in a real scenario under limited communication and time resources. This paper describes how the contest has been designed and analyzes the general progress of the attacks during the contest.